Climate change adaptation by ports: the attitude of Chinese port organizations. Issue 7 (2nd October 2020) - Lin, Yufeng; Ng, Adolf K. Y.; Zhang, Anming; Xu, Yimeng; He, Yile
ABSTRACT: Climate change poses a potential risk to coastal infrastructure, thus threatening the economics or even the safety of human beings. Thus, a better understanding of the attitude of port organizations toward climate adaptation and mitigation is essential. This paper addresses this research gap by investigating 18 port organizations in China. The questions include the impediments and the impact of context, systems, and other factors on the implementation of adaptation strategies. The results indicate that port organizations are generally aware of climate change impacts and agree that some further steps are needed. However, policy support serves as a key factor in implementing adaptation plans. Apart from offering important insight on the attitude of port organizations, the study also serves as a platform for further research on climate adaptation planning in China.